2019
DOI: 10.1177/1538192719832250
|View full text |Cite
|
Sign up to set email alerts
|

Is “Business as Usual” Enough to Be Hispanic-Serving? Becoming a Hispanic-Serving Research Institution

Abstract: This study focuses on an emerging Hispanic-Serving Research Institution (HSRI) and seeks to understand its Hispanic-serving identity as seen through the eyes of senior campus administrators. Findings suggest that instead of asking whether an institution is Hispanic-serving, it may be more appropriate to ask about the extent to which an institution is Hispanic-serving, acknowledging the ongoing identity development that may be required of institutions and supporting the need to expand the existing HSI (Hispanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…According to Excelencia in Education (2021), HSIs enroll 67% of the Latinx undergraduate student population across 569 campuses. Scholars (Garcia, 2019; Marin, 2019) and policy intermediaries (Excelencia in Education, 2021) have challenged HSI leaders to move beyond enrolling Latinx students to serving them. Yet this diversity within HSIs also makes understanding servingness for Latinx students a complex issue and not easily generalizable (Cuellar, 2019).…”
mentioning
confidence: 99%
“…According to Excelencia in Education (2021), HSIs enroll 67% of the Latinx undergraduate student population across 569 campuses. Scholars (Garcia, 2019; Marin, 2019) and policy intermediaries (Excelencia in Education, 2021) have challenged HSI leaders to move beyond enrolling Latinx students to serving them. Yet this diversity within HSIs also makes understanding servingness for Latinx students a complex issue and not easily generalizable (Cuellar, 2019).…”
mentioning
confidence: 99%
“…Adding these to the current number of 539 HSIs would represent a 65% increase in HSIs. To be responsive to student needs, these institutions will have to adjust their educational models in more culturally relevant directions to promote student success (Marin, 2019). It is critical that these institutions and others employ culturally relevant conceptual frameworks and practical strategies grounded in research about the very institutional contexts that have been especially successful in serving large numbers of Latinx and other racially minoritized students: MSIs and HSIs (Malcom-Piqueux, 2020;McGee, 2020a,b;NASEM, 2019;Núñez et al, 2021).…”
Section: Conclusion (Implications For Research Policy and Practice)mentioning
confidence: 99%
“…These skills must be developed through mentoring from a professional in the field who the student can engage with outside of the classroom. Unfortunately, many promising, talented URMs are overlooked by a selection process for Research Experience for Undergraduate (REU) programs that reproduce inequality (Figueroa, 2015;Kidder, 2013;Marin, 2019). In my work with students, I found that one fourth of these individuals had tried to join a faculty lab prior to their work with PMPS and were rejected due to high admission standards (often based on one-dimensional criteria like GPA) or a lack of experience or confidence in approaching faculty.…”
Section: Utilizing the Transformative Paradigm To "Open Doors" And Fo...mentioning
confidence: 99%
“…Including empowerment as a form of success for URMs stems from the transformative paradigm, which specifically calls to "disrupt commonly held assumptions that perpetuate privilege and exclude or render groups invisible" (Hurtado, 2015;Kezar & Lester, 2011). Empowerment can be assessed in students by taking into account important background characteristics that students bring to college with them and centering the experiences of students and faculty of color to examine the ways that institutionalized oppression has created inequality in student success (Cueller, 2015;Estepp et al, 2017;Marin, 2019;Monarrez et al, 2019). That URMs are deterred from the STEM environment because of the knowledge of bias is an example of how such imbedded inequality works to reproduce institutional oppression.…”
Section: The Transformative Paradigm and Institutional Changementioning
confidence: 99%